The von Willebrand factor Tyr2561 allele is a gain-of-function variant and a risk factor for early myocardial infarction - Schneppenheim, Reinhard; Huck, Volker; März, Winfried (Blood, 2019)
Visual Abstract. Download figureOpen in new tabDownload powerpoint. The frequent von Willebrand factor (VWF) variant p.Phe2561Tyr is located within the C4 domain, which also harbors the platelet GPIIb/IIIa-binding RGD sequence. To investigate its potential effect on hemostasis, we genotyped 865 patients with coronary artery disease (CAD), 915 with myocardial infarction (MI), and 417 control patients (Ludwigshafen Risk and Cardiovascular Health Study) and performed functional studies of this variant. A univariate analysis of male and female carriers of the Tyr2561 allele aged 55 years or younger revealed an elevated risk for repeated MI (odds ratio, 2.53; 95% confidence interval [CI], 1.07-5.98). The odds ratio was even higher in females aged 55 years or younger, at a value of 5.93 (95% CI, 1.12-31.24). Cone and plate aggregometry showed that compared with Phe2561, Tyr2561 was associated with increased platelet aggregate size both in probands’ blood and with the recombinant variants. Microfluidic assays revealed that the critical shear rate for inducing aggregate formation was decreased to 50% by Tyr2561 compared with Phe2561. Differences in C-domain circular dichroism spectra resulting from Tyr2561 suggest an increased shear sensitivity of VWF as a result of altered association of the C domains that disrupts the normal dimer interface. In summary, our data emphasize the functional effect of the VWF C4 domain for VWF-mediated platelet aggregation in a shear-dependent manner and provide the first evidence that a functional variant of VWF plays a role in arterial thromboembolism.